SYSTEMATIC REVIEW ON THE INFLUENCE OF FINANCIAL LITERACY, DIGITAL PAYMENT ADOPTION, AND PROMOTIONAL STRATEGIES ON CONSUMER SHOPPING BEHAVIOR THROUGH PURCHASE DECISIONS - Early Harison Mahardhika; Budi Eko Soetjipto; Ludi Wisnu Wardhana (RADJA PUBLIKA, 2025)
The digital transformation has fundamentally reshaped the dynamics of consumer shopping behavior, wherein financial literacy, the adoption of digital payment systems, and promotional strategies play a central role in shaping purchase decisions and consumption loyalty. This study aims to systematically synthesize the interrelations among financial literacy, digital payment adoption, and promotional strategies in influencing consumer shopping behavior, with purchase decision serving as an intervening variable. The approach employed is a Systematic Literature Review (SLR), screening literature from the Scopus database over the 2019–2024 period. Inclusion criteria comprise scholarly articles utilizing quantitative, qualitative, bibliometric, or conceptual methodologies. Following the selection process, a total of 93 articles were analyzed using thematic synthesis techniques. The primary findings from this synthesis include: (1) financial literacy reduces impulsive consumption tendencies and promotes rational decision-making; digital payment adoption enhances consumer trust, efficiency, and loyalty; promotional strategies delivered through social media, sustainability values (green values), gamification, and virtual reality (VR) marketing foster emotional engagement and behavioral intention to shop; and (2) purchase decision acts as a mediating variable that bridges the influence of various marketing stimuli on shopping behavior. This review reinforces the theoretical foundation of the cognitive-affective approach to consumer behavior and provides practical implications for the development of marketing strategies grounded in literacy, technology, and sustainability. Managerial implications include the design of financial education programs, personalization of digital promotions, and the strengthening of trust- and experience-based digital payment systems.